Serum exocrine pancreas enzymes are biomarkers of immunotherapy response in new-onset type 1 diabetes - Brittany Sorensen Bruggeman; Savanna Gornisiewicz; Rhonda Bacher; Kieran McGrail; Martha Campbell-Thompson; Clive Wasserfall; Laura M. Jacobsen; Laura M. Jacobsen; Mark Atkinson; Michael J. Haller; Desmond A. Schatz (Frontiers in Endocrinology)
IntroductionThe immune-mediated destruction of insulin-producing β-cells characterizes type 1 diabetes. Nevertheless, exocrine pancreatic enzymes, including amylase, lipase, and trypsin, are also significantly reduced in type 1 diabetes. With an immunotherapy now approved to treat early-stage type 1 diabetes, biomarkers to delineate response to treatment are needed. No study has yet evaluated whether serum exocrine pancreatic enzymes could delineate immunotherapy responders and non-responders.MethodsIn this novel study, we sought to identify longitudinal trends in the most commonly measured circulating exocrine enzymes before and after treatment with anti-thymocyte globulin (ATG) and pegylated granulocyte colony-stimulating factor (GCSF) in individuals with new-onset type 1 diabetes (n=34). We defined response to immunotherapy as participants with at least 60% of baseline area under the curve (AUC) C-peptide levels after a 2-hour mixed meal tolerance test (MMTT) at two years post-treatment. In the overall study (n=89), 42% of treated and 17% of placebo participants met this definition. Due to constraints of sample availability, we compared longitudinal serum amylase, lipase, and trypsin levels in a subset of responders to therapy (n=4-6), placebo “responders” (n=2), treated non-responders (n=16), and placebo non-responders (n=10).ResultsThere were no differences in amylase levels between groups at baseline or six months post-treatment. Baseline levels of lipase and trypsin tended to be lower in responders; however, these variations were not significant in this small study sample. Lipase and trypsin improved to 115% of baseline in responders to immunotherapy six months after treatment and declined to 80-90% of baseline in non-responders and placebo participants (p=0.03). This difference was not present before the six-month time point.DiscussionOur findings provide preliminary evidence that the exocrine pancreatic enzymes lipase and trypsin may be useful biomarkers of response to immunotherapy in type 1 diabetes. Further studies with larger numbers of participants are warranted.